Surface roughness analysis of four restorative materials exposed to 10% and 15% carbamide peroxide - Zavanelli, Adriana Cristina [UNESP]; Mazaro, José Vitor Quinelli [UNESP]; Silva, Cristina Ramos [UNESP]; Zavanelli, Ricardo Alexandre; Mancuso, Daniela Nardi (My University, 2011)
The aim of this study was to evaluate the effects of carbamide peroxide (CP) on surfaces of different restorative materials. Porcelain, composite resin, glass ionomer, and amalgam were analyzed in this study. Surface roughness (Ra) was measured before and after treatment with 10% and 15% CP. Fifteen percent CP increased Ra values in both the glass ionomer and amalgam subgroups, while 10% CP increased Ra values in the glass ionomer subgroup only. Changes in restorative material surfaces can be more severe when bleaching is completed without a clinician’s supervision. Hence, thorough patient examinations must be done before, during, and after bleaching treatment. © 2011 by Quintessence Publishing Co Inc.